2017
DOI: 10.1186/s12935-016-0370-x
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-embedded HuH-7 cells increase MMP-9 and reduce OCLN expression in vitro

Abstract: BackgroundHepatocellular carcinoma is a common cancer, ranking third in cancer-associated deaths. An important cause of cancer patients’ mortality is metastasis. At the start of metastasis progression, there is an epithelial-mesenchymal transition, characterized by matrix degradation, junction reductions and vessels formation. HuH-7 is a cell line used in research as an in vitro model for hepatocellular carcinoma. It is known that two-dimensional growth reflects tumor characteristics poorly. In contrast, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To enhance the stability of the microscaffolds over a longer period of time (>1 week), 1% alginate was added to all the compositions as the crosslinking agent. 31 This biopolymer was used for its high biocompatibility and reversible crosslinking ability in the presence of calcium ions. Alginate-based systems provide the benefit of extracting the cells from these scaffolds for further analysis by disrupting the calcium crosslinks.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the stability of the microscaffolds over a longer period of time (>1 week), 1% alginate was added to all the compositions as the crosslinking agent. 31 This biopolymer was used for its high biocompatibility and reversible crosslinking ability in the presence of calcium ions. Alginate-based systems provide the benefit of extracting the cells from these scaffolds for further analysis by disrupting the calcium crosslinks.…”
Section: Resultsmentioning
confidence: 99%
“…Originally developed for tissue engineering [ 16 , 17 ], cell microencapsulation with alginate hydrogels has been recently adopted as a suitable model for 3D in vitro culture in cancer researches [ 11 ]. Previous studies showed that alginate microencapsulation enhanced cancer cell proliferation and survival, modulated cancer cell migration and invasiveness and exacerbated tumor malignancies [ 14 , 15 , 18 21 ]. Our results demonstrated that alginate microencapsulation increased the proangiogenic potentials of low-passage poorly-differentiated human MEC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, multicellular tumor cell aggregates enabled cancer cells to experience a controlled 3D environment seen in solid tumors, where a gradient of chemical and critical biological signals, such as nutrients and oxygen, promote the assembly of “tumors tissue type” [ 15 ]. Therefore, cancer cells in 3D are under hypoxic conditions [ 15 , 21 ]. In contrast, low-passage poorly-differentiated human MEC cells in 2D monolayer culture are exposed to a uniform environment with sufficient availability of nutrients and oxygen [ 9 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation